EFFECTIVE IN VIVO CHOLESTEROL AND TRIGLYCERIDES LOWERING ACTIVITIES OF HYDROETHANOLIC EXTRACT OF LAUNAEA TARAXACIFOLIA LEAVES - AGBANGNAN DOSSA, COKOU PASCAL (My University, 2017)
Launaea taraxacifolia is a leaf vegetable consumed in several African countries including Nigeria, Ghana and Benin. It is eaten as salad, sauce and infusion to fight against certain diseases including liver diseases, diabetes and hypertension. The hydroethanolic extract of Launaea taraxacifolia leaves is rich in polyphenols (phenolic acids, flavonoids and tannins catechists) and would have antioxidant and hypolipidaemic activities. In this work we studied the effect of the hydroethanolic extract of the plant on blood sugar, cholesterol and triglycerides levels in Wistar rats. We also examined the effect of treatment on liver and kidney histology of treated rats to detect possible cytotoxic effects. Three groups of five Wistar rats were used for daily treatment during 15 days. The first group of control rats received water, the second group received 300mg per kg of body weight of extract and the third group received 500mg per kg of body weight. Our results showed that the doses of the extract used have no effect on blood glucose in rats. By cons we note a significant lowering effect on cholesterol and triglycerides levels by comparing the blood lipids levels in the control and treated rats. The hepatic and renal histology showed no visible atypia. Considering the direct link between cholesterol, triglycerides and heart diseases, regular consumption of Launaea taraxacifolia leaves may help to prevent cardiovascular diseases.
Keywords: Launaea taraxacifolia; Blood Glucose; Cholesterol; Triglycerides; Wistar Rats